Domestic work and psychological distress--what is the importance of relative socioeconomic position and gender inequality in the couple relationship? - Lisa Harryson (Public Library of Science (PLoS), 2012)
Aims The aim of this study was to investigate whether the relation between responsibility for domestic work and psychological distress was influenced by perception of gender inequality in the couple relationship and relative socioeconomic position. Methods In the Northern Swedish Cohort, all pupils who studied in the last year of compulsory school in a northern Swedish town in 1981 have been followed regularly until 2007. In this study, participants living with children were selected (n = 371 women, 352 men). The importance of relative socioeconomic position and perception of gender inequality in the couple relationship in combination with domestic work for psychological distress was examined through logistic regression analysis. Results Two combinations of variables including socioeconomic position ('having less than half of the responsibility for domestic work and partner higher socioeconomic position' and 'having more than half the responsibility for domestic work and equal socioeconomic position') were related to psychological distress. There were also higher ORs for psychological distress for the combinations of having 'less than half of the responsibility for domestic work and gender-unequal couple relationship' and 'more than half the responsibility for domestic work and gender-unequal couple relationship'. Having a lower socioeconomic position than the partner was associated with higher ORs for psychological distress among men. Conclusions This study showed that domestic work is a highly gendered activity as women tend to have a greater and men a smaller responsibility. Both these directions of inequality in domestic work, in combination with experiencing the couple relationship as gender-unequal, were associated with psychological distress There is a need for more research with a relational approach on inequalities in health in order to capture the power relations within couples in various settings.